Implementation of Green Logistics on the Development of Cargo Logistics in the Free Trade Zone Area: A Case Study of PT Bandara Internasional Batam - Muhammad Aditya Saputra; Desi Ratna Sari (Journal of Applied Business Administration, 2025)
This study examines the implementation of green logistics at PT Bandara Internasional Batam to evaluate its role in supporting the development of cargo logistics in the Free Trade Zone (FTZ) area. Using a qualitative case study approach, data were collected through in-depth interviews with key informants, direct field observations, and document analysis. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the adoption of green logistics practices at PT Bandara Internasional Batam has not yet been fully optimized. Although initiatives such as a semi-automated Warehouse Management System (WMS) and document digitalization (paperless system) have been introduced, significant barriers remain, including high investment costs, limited infrastructure, and insufficient human resource capacity. The analysis highlights that outdated cargo facilities, low environmental awareness among workers and service users, and incomplete digital transformation contribute to the slow progress of green logistics implementation. Comparisons with practices in other international airports demonstrate the importance of modern technology adoption, stronger regulatory support, and cultural change in advancing sustainable logistics. This study contributes theoretically by expanding knowledge on the application of green logistics in the aviation sector within a developing country context. Practically, it provides actionable recommendations for PT Bandara Internasional Batam, policymakers, and industry stakeholders to enhance operational efficiency, reduce environmental impact, and strengthen competitiveness in the FTZ area.